The Effect of Transformational Leadership, Training, and Compensation on the Performance of Family Planning Counsellor with mediating of Organizational Commitment - Reni Elina; Vidyarini Dwita; Erni Masdupi; Megawati Megawati (Eduvest - Journal of Universal Studies, 2024)
Purpose – The aim was to examine how transformational leadership, training, and compensation affect the employee performance of family planning counselors. The study also investigated whether organizational commitment plays a role in mediating this relationship. Methodology –The researchers used a stratified random sampling technique to select 155 family planning counselors as the sample size. The collected data was analyzed using the Smart PLS software version and the Partial Least Square (PLS) approach. Findings – The study revealed that organizational commitment acts as a mediator in the relationship between transformational leadership, training, compensation, and the performance of family planning counselors. Originality – This research examined organization commitment, which has a broad and significant impact on employee performance. It also provided better comprehension concerning the relationship of transformational leadership, training, and compensation on this study.